Cognition in the First Year After a Minor Stroke, Transient Ischemic Attack, or Mimic Event and the Role of Vascular Risk Factors - Nicolas, Korinne; Levi, Christopher; Evans, Tiffany-Jane; Michie, Patricia T.; Magin, Parker; Quain, Debbie; Bivard, Andrew; Karayanidis, Frini (Frontiers in Neurology, 2020)
Background— Cognitive impairment following a minor stroke or transient ischemic attack (TIA) is common, however, due to diagnostic difficulties, the prevalence and underlying cause of impairment remains poorly defined. We compared cognition in patients after a minor stroke, TIA or a mimic event at three timepoints in the first year following the event. We examine whether cognitive impairment occurs following these events and whether this impairment differs based on the event type. Further, we measure whether these findings persist after controlling for age, education and the presence of vascular risk factors and whether the presence of vascular risk factors, independent of event etiology, are associated with cognitive impairment. Lastly, we investigate whether increased stroke risk, as assessed by the ABCD2, is associated with reduced cognition. Methods—Medical information, a cognitive screening test and a measure of executive functioning were collected from 613 patients (123 minor stroke, 175 TIA and 315 mimics) using phone interviews at three time points in the first year following the event. Linear mixed models were used to determine the effect of event type, vascular risk factors and predicted stroke risk on cognitive performance while controlling for confounders. Results— There was no relationship between event type and performance on either cognitive measure. When controlling for all confounders, performance on the cognitive screening test was uniquely accounted for by the presence of heart failure, myocardial infarction, angina and hypertension (all p <.047), whereas the measure of executive functioning was uniquely accounted for by the presence of hypertension and angina (all p <.032). Increased stroke risk also predicted performance on the cognitive screening test and the measure of executive functioning (all p<.002). Conclusions— Our findings indicate that cognitive impairment following a minor stroke or TIA may be attributed to the high prevalence of chronic vascular risk factors in these patients. This highlights the importance of long-term management of vascular risk factors beyond event recovery to reduce the risk of cognitive impairment. Increased stroke risk (i.e., ABCD2 score) was also associated with reduced cognition, suggesting that it may be helpful in signaling the need for further cognitive evaluation and intervention post-event.